NÅGRA FUNDERINGAR KRING ÖVERSÄTTNING AV SVENSK POESI TILL POLSKA OCH ÖVERSÄTTNINGSKRITIK - Rosińska, Paulina (Folia Scandinavica Posnaniensia, 2017)
Inspired by the fact that there are as many as five different Polish translations of Gunnar Ekelöf’s poem Absentia animi (Non serviam, 1945), this paper aims to present and discuss several criteria that may be helpful to identify, describe and evaluate conditions, tendencies and strategies concerning Polish translations of Swedish poetry. The most crucial of the presented criteria, that may be used in order to ascertain what kind of poetry has been translated from Swedish into Polish so far, is the translator’s attitude to literary canons. It is based on Jerzy Jarniewicz’s distinction between two possible attitudes, i. e. ‘ambassador’ and ‘legislator’, which stand for respectively transferring the established canon from the source-language literature, and creating a new one that can influence the target-language literature. The other criteria discussed refer to the following questions: the affiliation of the translated text with either the source-language literature or the targetlanguage literature (1), the possibility of evaluation of poetry translation (2), and the concept of untranslatability (3). All of the mentioned criteria can help to analyze the specific strategies applied in the translation process. The paper is to be seen as an introduction to a larger ongoing research conducted by the author.